1995
DOI: 10.1007/bf00221390
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of ospA genes shows homogeneity within Borrelia burgdorferi sensu stricto and Borrelia afzelii strains but reveals major subgroups within the Borrelia garinii species

Abstract: The genes coding for the outer surface protein A (OspA) of 19 different Borrelia burgdorferi strains belonging to the seven OspA-serotypes 1-7, previously described [Wilske et al. (1993) J Clin Microbiol, 31: 340-350], have been investigated. B. burgdorferi sensu lato strains were chosen from various biological sources (ticks, human skin and cerebrospinal fluid) as well as different geographical origins (Germany, Slovenia, Austria, United States). The open reading frames of all ospA genes consist of 819-825 nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 42 publications
4
73
0
2
Order By: Relevance
“…[24][25][26][27] Nucleotide sequence variation of a target gene may actually represent the genetic distance of phylogenetic divergence between or within the genospecies of Borrelia isolates. 27,31,34,35 In this study, the phylogenetic analysis of OspA gene demonstrates a high sequence homogeneity among Borrelia isolates within the genospecies of B. burgdorferi sensu stricto, and all of the Taiwan isolates exhibit almost identical nucleotide sequences of OspA gene (see Table 3). Further investigation of the sequence anlysis of other target genes, such as the genes encoding the OspC and 5S-23S intergenic spacer region, of these Taiwan isolates would help to elucidate the genetic divergence of Borrelia isolates in Taiwan.…”
Section: Discussionmentioning
confidence: 61%
“…[24][25][26][27] Nucleotide sequence variation of a target gene may actually represent the genetic distance of phylogenetic divergence between or within the genospecies of Borrelia isolates. 27,31,34,35 In this study, the phylogenetic analysis of OspA gene demonstrates a high sequence homogeneity among Borrelia isolates within the genospecies of B. burgdorferi sensu stricto, and all of the Taiwan isolates exhibit almost identical nucleotide sequences of OspA gene (see Table 3). Further investigation of the sequence anlysis of other target genes, such as the genes encoding the OspC and 5S-23S intergenic spacer region, of these Taiwan isolates would help to elucidate the genetic divergence of Borrelia isolates in Taiwan.…”
Section: Discussionmentioning
confidence: 61%
“…Este sería el caso de la genoespecie identificada en Yucatán, B. garinii, conocida por ser la más heterogénea de todas las especies del complejo B. burgdorferi s.l. (46,47).…”
Section: Discussionunclassified
“…The hete rogeneity of the causative strains is a challenge for the microbiological diagnosis of Lyme borreliosis in Europe. The heterogeneity observed among ospA sequences of European strains (especially regarding B. garinii), has been used for the development of diagnostic tools (Wilske et al, 1993;Will et al, 1995;Michel et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the correspondence of strains to OspA serotype types the obtained sequences were compared with the strains of serotypes described for B. garinii (Wilske et al, 1993;Will et al, 1995;Wilske et al, 2007) from GenBank. Among the 13 ospA sequences obtained from ticks in this study, 5 different genotypes were identified.…”
Section: Sequence Analysismentioning
confidence: 99%